PERLINDUNGAN HAK CIPTA TUGU SELAMAT DATANG (STUDI PUTUSAN NOMOR: 35/PDT.SUS-HAK CIPTA/2020/PN NIAGA JKT. PST. - Sandra Gloria Satriani; R. Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2022)
Intellectual property is a material right, the right to an object that originates from the work of thebrain, and the work of ratios. Intellectual property in law is divided into 2 groups, namely the right tomanufacture (copyright) and factory property rights (industrial property rights). Copyright is definedas the exclusive right of the creator that arises automatically based on declarative principles after thecreation is manifested in a tangible form without restrictions in accordance with the provisions of lawsand regulations. The author uses normative legal research methods and uses interview data assupporting data. The results of the study reveal that copyright protection for the Selamat DatangMonument sketch and Selamat Datang Monument statue is regulated in Law Number 28 of 2014concerning Copyright. Court Decision Number 35/Pdt.Sus-Hak Cipta/2020/PN Niaga Jkt.Pst isinconsistent with the provisions of the existing laws and regulations. The sketch of the Selamat DatangMonument and the Selamat Datang Monument statue were created because of an order from PresidentSoekarno to Henk Ngantung (in his capacity as Deputy Governor of Jakarta) and Edhi Sunarso.Therefore, the creation was made because of the framework of the working relationship and the orderthat was made because it was under the creation of the creation the sketch of the Selamat DatangMonument and the statue of the Selamat Datang Monument should be recognized as fully stateproperty.